The Potential of Rural–Urban Linkages for Sustainable Development and Trade - Akkoyunlu, Şule (International Journal of Sustainable Development & World Policy, 2015)
Rural–urban linkages play a crucial role in the generation of income, employment and wealth. Yet, for various reasons the importance of such linkages is not recognized and thus ignored in national economic and trade policies. The present paper investigates infrastructure problems, institutional constraints and trade barriers that tend to discourage linkages between rural and urban regions and thus prevent a process of rural empowerment and economic development. The findings of our review indicate that clustering rural and urban areas into regional planning units may create the necessary enabling environment for extended trade networks and knowledge exchange between the city and the countryside. As such, stronger rural–urban linkages could also play a crucial role in poverty reduction in developing countries.